Indian Rural Marketing - Challenges, Opportunities And Strategies For The Marketeers (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The Indian rural market is becoming lucrative and  demanding both for the companies and the customers. It is  filled with challenges and opportunities both. On one hand,  there are specific characteristics of the rural market which  stops the companies to enter and perform on the other  hand the market invites great business volumes in terms of  population and its uniqueness.
Keywords: Literacy; Rural; Potential; Price Perception; Socio – Psychological